Persepsi Terhadap Perbankan Syariah di Kalangan Mahasiswa Manajemen UNISBA: Sebuah Studi Analisis - Millatul Fadhilah; Roichatul Mabruroh (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to explore the perceptions of management students at Universitas Islam Bandung (UNISBA) regarding Islamic banking. A qualitative approach was employed, utilizing in-depth interviews and focus group discussions for data collection. The results indicate that students' understanding of the principles of Islamic banking varies, with some students demonstrating a strong grasp due to formal education, while others exhibit limited awareness. Additionally, factors such as religious beliefs and financial literacy significantly influence their perceptions. Experiences with Islamic banking products also vary, with many students expressing a preference for conventional banks due to convenience. This research suggests the need for enhanced education and marketing strategies by Islamic banks to attract the attention of the younger generation.